Severe Patients With ARDS With COVID-19 Treated With Extracorporeal Membrane Oxygenation in China: A Retrospective Study - Lai, Wei; Li, Shuanglei; Du, Zhongtao; Ma, Xinhua; Lu, Junyu; Gao, Wei Dong; Abbott, Geoffrey W.; Hu, Zhaoyang; Kang, Yan (Frontiers in Medicine, 2021)
Background: The novel coronavirus (COVID-19) pandemic has become a global health crisis affecting over 200 countries worldwide. Extra-corporeal membrane oxygenation (ECMO) has been increasingly used in the management of COVID-19-associated end-stage respiratory failure. However, the exact effect of ECMO in the management of these patient, especially with regards to complications and mortality, is unclear. Methods: This is the largest retrospective study of ECMO treated COVID-19 patients in China. A total of 50 ECMO-treated COVID-19 patients were recruited. We describe the main characteristics, the clinical features, ventilator parameters, extracorporeal membrane oxygenation (ECMO)-related variables and management details, complications and outcomes of COVID-19 patients with severe ARDS that required ECMO support. Results: For those patients with ECMO support, 21 patients survived and 29 died(mortality rate: 58.0%). Among those that survived,PaO2 (66.3mmHg [59.5-74.0 mmHg] and PaO2/FiO2 (68.0mmHg [61.0-76.0 mmHg]) were higher in survivors than those of non-survivors (PaO2: 56.8 mmHg (49.0-65.0 mmHg), PaO2/FiO2 (58.2 mmHg (49.0-68.0 mmHg), all P<0.01) prior to ECMO. Patients who achieved negative fluid balance in the early resuscitation phase (within 3 days) had a higher survival rate than those who did not (P=0.0003). Conclusions: In this study of 50 cases of ECMO-treated COVID-19 patients, low PO2/FIO2 ratio before ECMO commencement may indicate a poor prognosis. Negative fluid balance in the early resuscitation phrase during ECMO treatment was a predictor of increased survival post-ECMO treatment.